Does Restaurant Menu Information Affect Costumer Attitude and Behavioral Intention? An Empirical Analysis in Time of Pandemic COVID-19 - Bawono, Anton (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2024)
This study aims to see the effect of providing important information for consumers on restaurant menus by adding variables related to health and safety issues during the COVID19 pandemic. Overall this study obtained a response of 574, but only 559 that can be carried out further testing. We use the Structural Equation Model (SEM)-Partial Least Square (PLS) is conducted for data analysis to verify the relationship between variables. This study found that in general the provision of information on restaurant menus has a positive impact on the formation of attitude and behavior intention. Variables related to security, health and halal issues are consistently proven to be influential and have the highest effect size. This research is a complement to previous research, thereby strengthening the formation of attitude and behavioral intention towards restaurant consumers. Moreover, in the midst of the difficult pandemic period, especially for the restaurant industry, strengthening direct sales with the formation of attitude and behavior intention is one step to supply revenue to the company's cash. This study is one of few studies that has focused on providing important information on restaurant menus, which are extensions of attributes. This study also adds variables related to COVID-19 and Halal to strengthen the resulting predictive power.